The Fund's Lending Framework and Sovereign Debt-Further Considerations. (Policy Papers; Policy Paper ;, 2015)
In discussing the June 2014 paper, Executive Directors broadly supported staff's proposal to introduce more flexibility into the Fund's exceptional access framework to reduce unnecessary costs for the member, its creditors, and the overall system. Directors' views varied on staff's proposal to eliminate the systemic exemption introduced in 2010. Many Directors favored removing the exemption but some others preferred to retain it and requested staff to consult further with relevant stakeholders on possible approaches to managing contagion. This paper offers specific proposals on how the Fund's policy framework could be changed, presents staff's analysis on the specific issue of managing contagion, and addresses some implementation issues. No Board decision is proposed at this stage. The paper is consistent with the Executive Board's May 2013 endorsement of a work program focused on strengthening market-based approaches to resolving sovereign debt crises.